KINERJA LAPISAN PENUTUP LEMPUNG STABILISASI SEMEN PADA BANGUNAN SANITARY LANDFILL - galung, erwin (FORUM BANGUNAN, 2014)
Sanitary Landfill is a landfill with trash landfill in layers on land that has been prepared, leveled and compacted, then covered with soil cover each end of the operation. When rainwater infiltrating the landfill surface and water flows out of the landfill will bring a variety of mineral and organic matter in the form of suspension cannot be separated. Final cover on the land application heap plays an important role; the infiltration rate of the cover can be minimized in various ways such as by modifying the composition of the cover layer material (Clay Cover) on Sanitary Landfill. This study examined the performance of the sanitary landfill cover. Varying the amount of soil cement mixed PCC as overburden is o%, 5%, 10%, 15%, and 20%. The parameter used is the value of the water content in each variation of the cover layer.Keywords: sanitary landfill, stabilization, clay, final cover